Avaliação da qualidade do leite cru refrigerado de silos de estocagem em laticínios do estado de Goiás - Barbosa, Valessa Teixeira (2020)
Bovine milk is the main raw material for dairy production and has a high nutritional value, as it provides essential nutrients for human nutrition. Although the dairy industry strictly controls microbial quality along milk processing lines, a large number of bacteria that can cause changes in its quality are identified during storage in silos. Therefore, this work aimed to evaluate the quality of refrigerated raw milk in storage silos in dairy industries in the state of Goiás and to study the influence of storage time and temperature on the growth of microorganisms during the silo emptying process for the processing of milk. Six dairy industries were selected in the state of Goiás, where one or two storage silos were randomly chosen for monitoring during the emptying of the silo. Samples were collected during the emptying of each silo, in duplicate, every thirty minutes. Milk samples from the same silos were also evaluated during simulation of a temperature increase of 2 to 7 ° C. The duration of emptying of the silo was evaluated; the temperature at the beginning of the process and every 30 minutes until the end of the process and the volume of milk in the silo or storage tank. The physicochemical characteristics (alizarol 72% stability, pH, titratable acidity, fat, protein, lactose, total solids, and non-fat total solids) and the microbiological characteristics (total bacterial count, aerobic count, psychrotrophic, total coliforms and E. coli). It was possible to observe that the majority of the industries still have difficulties in maintaining the temperature of the milk in the storage silos below 4 ° C, with TBC within the allowed by the Brazilian law. It was observed that the time interference during the emptying of the storage silo on the milk quality was more significant than the increase in temperature. It is possible to affirm that it is necessary to guarantee the conditions that minimize the growth of microorganisms since obtaining the milk so that there is less impact on the quality of the milk and dairy products